1991
DOI: 10.1007/bf01403200
|View full text |Cite
|
Sign up to set email alerts
|

Non-missile penetrating injuries of the spine

Abstract: Non-missile penetrating injuries of the spine accounted for 7% of all spinal injuries admitted to this Institute during the last 10 years. Young males were most commonly affected and 73% of the injuries involved the upper dorsal und cervical spine. They presented with varying degrees of neurological deficit. Plains x-rays revealed the bony injury and/or the retained foreign body satisfactorily. Myelography (with or without CT scan) was performed in patients with progressive neurological deterioration and those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 5 publications
1
72
0
5
Order By: Relevance
“…4 In most cases the weapon is withdrawn by the attacker. Rarely, in some patients the weapon or a part of it can still be lodged in place, which needs to be removed.…”
Section: Discussionmentioning
confidence: 99%
“…4 In most cases the weapon is withdrawn by the attacker. Rarely, in some patients the weapon or a part of it can still be lodged in place, which needs to be removed.…”
Section: Discussionmentioning
confidence: 99%
“…Penetran spinal yaralanmalarda lokal yara bakımı, analjezi, geniş spektrumlu antibiyotik ve tetanoz proflaksisi tavsiye edilmektedir. Kanal içinde yabancı cisim ya da kemik fragmanları varlığında, epidural yada intradural abse ve 4 günden daha uzun süren BOS kaçağı varlığında cerrahi girişim önerilmektedir (10)(11)(12) . Olgumuzda ilk başvurduğu hastanede lokal yara bakımı yapılmış.…”
Section: Discussionunclassified
“…2) A recent study found 22% of penetrating spinal injuries occurred in the thoracic region, and 23 of 84 patients with thoracic penetrating injuries had associated visceral injury. 7) Gunshot wounds cause most penetrating spinal injuries, but stab wounds cause 7-26% of all penetrating spinal injuries, [5][6][7] and seem to be more frequent in thirdworld countries. 3) Stab injuries most commonly occur in young men, and usually involve the cervical and upper dorsal spine.…”
Section: Discussionmentioning
confidence: 99%
“…3) Stab injuries most commonly occur in young men, and usually involve the cervical and upper dorsal spine. 5) Penetrating injuries to the thoracic great vessels occur in 2% of cases of stab wounds to the chest, 1) but combined injury of both spinal cord and aorta by a dorsally placed stab is extremely rare. 4) Injuries to the great vessels are the most dangerous penetrating thorax traumas.…”
Section: Discussionmentioning
confidence: 99%